Thực hiện theo các bước sau :
Bước 1 : Biến đổi :
\(a_1\sin x+b_1\cos x=A\left(a_2\sin x+b_2\cos x\right)+B\left(a_2\cos x-b_2\sin x\right)\)
Bước 2 : Khi đó :
\(I=\int\frac{A\left(a_2\sin x+b_2\cos x\right)+B\left(a_2\cos x-b_2\sin x\right)}{\left(a_2\sin x+b_2\cos x\right)^2}dx=A\int\frac{dx}{a_2\cos x+b_2\sin x}+B\int\frac{\left(a_2\cos x+b_2\sin x\right)dx}{\left(a_2\cos x+b_2\sin x\right)^2}\)
\(=\frac{A}{\sqrt{a^2_2+b^2_2}}\int\frac{dx}{\sin\left(x+\alpha\right)}-B\int\frac{1}{a_2\sin x+b_2\cos x}dx=\frac{A}{\sqrt{a^2_2+b^2_2}}\ln\left|\tan\left(\frac{x+\alpha}{2}\right)\right|-\frac{B}{a_2\cos x+b_2\sin x}+C\)
Trong đó : \(\sin\alpha=\frac{b_2}{\sqrt{a^2_2+b^2_2}_{ }};\cos\alpha=\frac{a_2}{\sqrt{a^2_2+b^2_2}}\)